1990
DOI: 10.1016/0248-4900(90)90349-8
|View full text |Cite
|
Sign up to set email alerts
|

Acid secretion and membrane reorganization in single gastric parietal cell in primary culture

Abstract: A digitally-enhanced videomicroscopy study of rabbit gastric parietal cells in primary culture was performed using alternate observations with differential interference contrast and fluorescence optics of cells mounted and perfused on a temperature-controlled microscope stage. The effect of histamine, a physiological effector of acid secretion, was followed. Isolated parietal cells possess an internal apical vacuole, which kept the cell in a pseudopolarized state. This apical vacuole is a site of acid secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
4
17
0
Order By: Relevance
“…For some systems it is believed that vesicular transport is directed by microtubular motor proteins, such as kinesin, in an ATP-dependent manner (for review see McNiven and Marlowe 1999), but it still remains to be clarified whether and which motor proteins exist and operate on the microtubules in gastric parietal cells. Stimulation-associated volume expansions have been previously observed in the internalized apical membrane vacuoles of cultured parietal cells (Chew et al 1989;Mangeat et al 1990). It has been proposed that the volume expansion was due to the concomitant secretion of hydrochloric acid and water (Mangeat et al 1990).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For some systems it is believed that vesicular transport is directed by microtubular motor proteins, such as kinesin, in an ATP-dependent manner (for review see McNiven and Marlowe 1999), but it still remains to be clarified whether and which motor proteins exist and operate on the microtubules in gastric parietal cells. Stimulation-associated volume expansions have been previously observed in the internalized apical membrane vacuoles of cultured parietal cells (Chew et al 1989;Mangeat et al 1990). It has been proposed that the volume expansion was due to the concomitant secretion of hydrochloric acid and water (Mangeat et al 1990).…”
Section: Discussionmentioning
confidence: 96%
“…Stimulation-associated volume expansions have been previously observed in the internalized apical membrane vacuoles of cultured parietal cells (Chew et al 1989;Mangeat et al 1990). It has been proposed that the volume expansion was due to the concomitant secretion of hydrochloric acid and water (Mangeat et al 1990). In the present study, extensive volume expansion was also observed in the glandular lumen of some histaminestimulated glands, suggesting an accumulation of glandular secretory products, e.g., hydrochloric acid, mucin, zymogen.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2A,B. Several laboratories commonly report that cultured parietal cells take on a different morphological form than in situ (Agnew et al, 1999;Chew, 1994;Mangeat et al, 1990). After a few hours in culture the apical membrane is sequestered in the form of easily identified vacuoles (2-5 m in diameter), which we refer to as apical membrane vacuoles.…”
Section: Expression Of Cfp-ezrin Wt T567a and T567d Mutants In Gastrmentioning
confidence: 99%
“…Because the surrounding plasma membrane continues to serve as the site of receptor-mediated cell activation events, we refer to it as the basolateral membrane. Cultured parietal cells continue to maintain a secretagogue-dependent phenotype whereby H,KATPase-rich tubulovesicles are translocated to, and fuse with, apical membrane vacuoles and the resulting secretion of HCl produces gross vacuolar enlargement (Agnew et al, 1999;Mangeat et al, 1990;Zhou et al, 2003b). From the images of resting cells (i.e.…”
Section: Expression Of Cfp-ezrin Wt T567a and T567d Mutants In Gastrmentioning
confidence: 99%